CONSERVATION OF COCONUT TREE sap (COCOS NUCIFERA) BASED ON THE IMPACT ON HEALTH AND THE WAY OF PRODUCTION IN TAROK VILLAGE, SUB-DISTRICT 2 X 11 KAYU TAMAN - Febrianto Febrianto; Karina Netashia (SEMESTA: Journal of Science Education and Teaching, 2021)
jurnal tuak